2013
DOI: 10.1063/1.4794099
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ohmic contacts to plasma etched n-Al0.5Ga0.5N by annealing under nitrogen ambient before metal deposition

Abstract: The contact characteristics of Ti/Al and Ti/Al/Ni/Au contacts to as-grown, plasma etched and plasma etched + annealed in N2 n-Al0.5Ga0.5N epilayers were compared. After a rapid thermal annealing, both Ti/Al and Ti/Al/Ni/Au contacts to as-grown and plasma etched + annealed in N2 n-Al0.5Ga0.5N became truly Ohmic, whereas the contacts to plasma etched samples still remained rectifying. Surface atomic concentration analysis indicates the N vacancies resulting from plasma treatment act more as deep-level states rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Although the ICP-etching damage is inevitable and unfavorable for the ohmic contact, the high enough electron concentration can counteract the negative effects, and hence simplify the fabrication process of DUV-LEDs by omitting the treatment after etching. 27,28 Moreover in terms of the electron mobility, there is an obvious difference between the two samples, i.e., the mobility of n-AlGaN on 0.2°miscut sapphire (36.1 cm 2 V −1 s −1 ) is about 25% lower than that on 0.5°one (47.9 cm 2 V −1 s −1 ). The low mobility is inferred to originate from the grain boundary scattering of islands as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ICP-etching damage is inevitable and unfavorable for the ohmic contact, the high enough electron concentration can counteract the negative effects, and hence simplify the fabrication process of DUV-LEDs by omitting the treatment after etching. 27,28 Moreover in terms of the electron mobility, there is an obvious difference between the two samples, i.e., the mobility of n-AlGaN on 0.2°miscut sapphire (36.1 cm 2 V −1 s −1 ) is about 25% lower than that on 0.5°one (47.9 cm 2 V −1 s −1 ). The low mobility is inferred to originate from the grain boundary scattering of islands as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the ICP-etching damage is inevitable and unfavorable for the ohmic contact, the high enough electron concentration can counteract the negative effects, and hence simplify the fabrication process of DUV-LEDs by omitting the treatment after etching. 27,28…”
Section: Resultsmentioning
confidence: 99%
“…These results are comparable to the trends observed in other reports, which have demonstrated that a lower N/Ga ratio leads to the generation of N vacancies. 28,29 N vacancies located at a shallow energy level E D of approximately 25 meV below the conduction band in GaN are well-known for acting as donors. 30 In the presence of Ga vacancies (V Ga ), the low N/Ga ratio may also be explained by the fact that the generation of N vacancies is more pronounced than that of Ga out-diffusion during the LBSD process.…”
Section: Resultsmentioning
confidence: 99%
“…The epitaxial wafer was etched by using the Cl 2 and BCl 3 mixed gas in the inductively coupled plasma (ICP) system to expose the n-AlGaN layer [17], [18]. The Ti/Al/Ti/Au and Ni/Au/Ni/Au served as the n-and p-electrodes, respectively [19], [20]. The schematic diagram for the cross-section view and the micro-chip fabrication flow of the DUV devices are shown in Fig.…”
Section: Structures and Parametersmentioning
confidence: 99%